Pengembangan Multimedia Mendongeng pada Anak Usia Dini - Anisa Aditya Larasati; Afif Luthfy, Perdana; Wahyu Pusari, Ratna (Generasi Emas, 2024)
The use of multimedia learning media can be an effective means of improving the storytelling abilities of young children. By utilizing multimedia, children are not only actively involved in the learning process, but also develop creativity, imagination and speaking skills. Focusing on the needs and characteristics of children in the early stages of development is key in the process of developing learning media. This research aims to create interactive multimedia storytelling, specifically designed to improve storytelling skills in early childhood. This research uses the Research and Development (R&D) research method by applying the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to ensure success. development process. This multimedia storytelling is not only designed to provide an interesting and interactive learning experience, but also involves young children as test subjects. The research results show that there is success in developing multimedia storytelling in Sultan Fatah Demak Kindergarten class B aged 5-6 years through the CapCut application as an effective tool in facilitating multimedia learning. Product validation by media experts confirms a high level of validity. Meanwhile, field trials at the Sultan Fatah Demak Kindergarten obtained very good results with